Development and Validation of Stability Indicating Method for Estimation of Buparvaquone by Forced Degradation Studies - Kutubuddin, Shaikh Tanveer; Suresh, Shelke Sushil; Baliram, Kakde Rajendra; Aikaterini, Lalatsa (Indian Journal of Pharmaceutical Education and Research, 2020)
Aim: A lucid, rapid and precise stability-indicating method was developed by using HPLC for the estimation of Buparvaquone in bulk as well as pharmaceutical dosage form by forced degradation studies. Materials and Methods: Princeton C18 column (4.6 × 150 mm, 5μ) and mobile phase containing 1% glacial acetic acid and acetonitrile in the proportion of 5:95 v/v was used throughout the study. The flow rate was 0.9 ml/m and the detecting wavelength was kept as 251 nm using the PDA detector. Results: The retention time of Buparvaquone was found to be at 8.6 ± 0.5 m. The method developed was validated, as stated in ICH Q2 (R1) guidelines. It was found to be linear within concentration ranging from 2-20 μg/ml having a correlation coefficient 0.999 and other parameters are also under permissible limits. Conclusion: Buparvaquone was exposed to different stress conditions like acidic, basic, neutral, thermal, peroxide and also photolytic. Amongst all, the drug was found to be more degraded under basic as well as peroxide conditions.
Keywords: Buparvaquone; Forced degradation; Validation; RP-HPLC; Stability